2002
DOI: 10.5254/1.3547670
|View full text |Cite
|
Sign up to set email alerts
|

Cracking Energy Density as a Predictor of Fatigue Life under Multiaxial Conditions

Abstract: Rubber parts in service often experience complex strain histories that can cause mechanical failure. The ability to predict the effects of complex strain histories on fatigue life is therefore a critical need. This paper presents recent results of cyclic, combined tension/torsion fatigue experiments, and compares them with predictions based on a new parameter, the Cracking Energy Density. The Cracking Energy Density is the stored elastic energy density that is available to a crack on a given material plane, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
101
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 0 publications
1
101
0
Order By: Relevance
“…Some authors proposed the use of maximum principal stretch (λmax) [13,14], maximum principal Cauchy stress (tmax) [15] or strain energy density (W) [16,17] as predictors of rubber fatigue. More recently, several sophisticated multi-axial fatigue life predictors, based on critical plane-based approaches, have been developed for rubbers [18,19]. However, predictions of the fatigue properties of elastomeric materials and components are still imperfect because of their complex mechanical behaviour, especially for emerging smart materials like MREs.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors proposed the use of maximum principal stretch (λmax) [13,14], maximum principal Cauchy stress (tmax) [15] or strain energy density (W) [16,17] as predictors of rubber fatigue. More recently, several sophisticated multi-axial fatigue life predictors, based on critical plane-based approaches, have been developed for rubbers [18,19]. However, predictions of the fatigue properties of elastomeric materials and components are still imperfect because of their complex mechanical behaviour, especially for emerging smart materials like MREs.…”
Section: Introductionmentioning
confidence: 99%
“…The main idea in the latter approaches is that the forces driving failure are evaluated for each possible failure plane of the material, in order to identify the plane on which the most damaging forces occur. [88][89][90][91][92][93][94][95] Concerning the limitations of the energy limiters approach, we should mention that more experimental data are needed for the general validation and possible revision of the theory. Such revisions might be necessary for dynamic problems, fatigue, cases in which a significant amount of energy can be stored in ways that do not contribute to crack growth, and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…It provides a basis for determination of the growth rate of fatigue crack in rubber. Furthermore, Mars [12] carried out the cyclic and combined tension/torsion fatigue experiment of rubber, and compared the experimental results with the cracking energy density. It is found that the cracking energy density can be used to predict the effect of the complex strain history on fatigue life.…”
Section: Introductionmentioning
confidence: 99%